**Q: Solve for x: -2(4x-3)+5=-53**

A: The goal is to get “x” by itself. To do this, we need to start moving things aroumd:

-2(4x-3)+5=-53

[multiply -2 into the parentheses]:

-2(4x-3)+5=-53

-8x + 6 + 5 = -53

[combine the 5 & 6]

-8x + 11 = -53

[subtract 11 from both sides]

-8x + 11 – 11 = -53 – 11

-8x = -64

[divide both sides by -8]

-8x/-8 = -64/-8

x = 8

TADA

### Like this:

Like Loading...

Omg thanks soo much!this helped a lot like you have no idea!!this problem seemed so much clearer how you explained it to me!!Samantha<33

LikeLike